Fintech Peer-to-Peer Lending in Digital Financial Applications from the Perspective of Maqashid Shariah - Nafisha Asyifana; Fitriani, Ajeng Pipit (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: Currently, humanity is in the era of Society 5.0, characterized by the concept of humanizing humans with technology. This era enables humans to derive benefits from technological advancements. The emergence of fintech represents a breakthrough and innovation in the field of financial services, providing both financial solutions and intermediation. This research aims to determine the implementation of maqashid shariah in fintech peer-to-peer (P2P) lending, assess the impact of implementing maqashid shariah in fintech P2P lending, and examine the relevance of fintech P2P lending to the development of shariah banking. Research Method: This study is a type of library research employing a qualitative approach. Data collection techniques include interviews and documentation. The research findings indicate that PT Ammana Fintek Syariah's fintech P2P lending aligns with the principles of maqashid shariah. Results: It has been demonstrated that Ammana Shariah fintech has fulfilled the five maqashids of shariah: protecting of religion, protecting of life, protecting of lineage, protecting of intellect, and protecting of property. Conclusion: The implementation of maqashid shariah in fintech P2P lending at Ammana has two main impacts: first, the impact on business actors, and second, the impact on fund owners. The presence of fintech encourages shariah banking to innovate in technology, thereby enhancing financial services and evaluating business models.